Does self-focus orientation influence recall of autobiographical memories and subsequent mood in dysphoria?. Issue 3 (16th March 2021) - Quigley, Leanne; Horne, Sarah J.; Dobson, Keith S.
ABSTRACT: Past research suggests that depressed individuals are less likely than non-depressed individuals to engage in mood-incongruent recall in response to negative mood and do not experience associated mood reparative effects. The present study examined the effects of adopting a reflective versus ruminative self-focus orientation towards one's mood on the valence of autobiographical memories recalled following a negative mood induction and the extent of mood repair following memory recall among individuals with varying depressive symptomatology. Participants underwent a negative mood induction and either a ruminative ( n = 69) or reflective ( n = 49) self-focus manipulation, and then recalled five specific autobiographical memories. Depression symptoms were associated with recall of less positive memories and reduced mood repair. The valence of recalled memories was associated with the extent of mood improvement, and depressive symptoms did not moderate this association. Contrary to our hypothesis, a reflective self-focus was not associated with recall of more positive memories or greater mood improvement than a ruminative self-focus. The results suggest that more depressed individuals are less likely to spontaneously engage in mood-incongruent recall in a negative mood state; however, recall of positive memories is associated with similar mood reparative effects regardless of depressive symptomatology.